PENGARUH MEDIA WORKSHEET TERHADAP MOTIVASI BELAJAR SISWA KELAS II PADA MATA PELAJARAN MATEMATIKA - Jannah, Nur Zahrotul; Bahrodin, Ariga (Universitas Islam Darul 'Ulum Lamongan, 2024)
Students often portray mathematics as a tedious and difficult topic. For pupils who get bored or tired of math quickly, this makes it difficult for teachers to explain the subject. Disengaging from these issues necessitates creative approaches to media selection in an effort to boost students' interest in and retention of course content. Media such as worksheets, in which students color pictures corresponding to the numerical values, serve as a link between mathematics and students. After then, they should respond to the questions. The quantitative method of experimental design, specifically the posttest-only control model, is employed in this study. This research focuses on 42 pupils from class II at MI Darul Urum Jogoroto Jombang. We used a purposive sampling strategy to do our sampling. Surveys, observations, and written records are the main tools for gathering information. Using SPSS 16, we ran a t-test on the data we gathered. The Mann Whitney test was used to acquire the research results, specifically a sig value of 0.014 < 0.05. This leads us to conclude that Ha is correct and H0 is false. Based on these findings, we can say that the media used in worksheets affects the motivation of second-year mathematics students at MI Darul Ulum 2 Jogoroto Jombang to study